2007
DOI: 10.1128/aem.01978-06
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Multiheme Protein with Features of a Hydrazine-Oxidizing Enzyme from an Anaerobic Ammonium-Oxidizing Enrichment Culture

Abstract: A multiheme protein having hydrazine-oxidizing activity was purified from enriched culture from a reactor in which an anammox bacterium, strain KSU-1, was dominant. The enzyme has oxidizing activity toward hydrazine but not hydroxylamine and is a 130-kDa homodimer composed of a 62-kDa polypeptide containing eight hemes. It was therefore named hydrazine-oxidizing enzyme (HZO). With cytochrome c as an electron acceptor, the V max and K m for hydrazine are 6.2 ؎ 0.3 mol/min · mg and 5.5 ؎ 0.6 M, respectively. Hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(115 citation statements)
references
References 32 publications
2
109
0
1
Order By: Relevance
“…(van der Star et al, 2008), thus making this genus more abundant and active in the habitats with high substrates input such as paddy soils. Furthermore, a recent study on the biogeography of anammox bacteria based on data from both natural and engineered ecosystems indicated that Candidatus Brocadia and Kuenenia are the closest co-occurring groups among the five genera, which implies that these genera would share similar habitats (Sonthiphand et al, 2014). Comparing to other four genera, Candidatus Scalindua was observed to be favorable to high salinity environments such as oceans and marine sediments (Dale et al, 2009), which partially explained its absence in the tested soils in this study.…”
Section: Detection Of Anammox Bacteria In Paddy Soilssupporting
confidence: 47%
See 2 more Smart Citations
“…(van der Star et al, 2008), thus making this genus more abundant and active in the habitats with high substrates input such as paddy soils. Furthermore, a recent study on the biogeography of anammox bacteria based on data from both natural and engineered ecosystems indicated that Candidatus Brocadia and Kuenenia are the closest co-occurring groups among the five genera, which implies that these genera would share similar habitats (Sonthiphand et al, 2014). Comparing to other four genera, Candidatus Scalindua was observed to be favorable to high salinity environments such as oceans and marine sediments (Dale et al, 2009), which partially explained its absence in the tested soils in this study.…”
Section: Detection Of Anammox Bacteria In Paddy Soilssupporting
confidence: 47%
“…The preference of alkaline soils by anammox bacteria could be explained by the characteristic of their enzymes. For instance, the hydrazine oxidizing enzyme (HZO), which catalyzes the final step of anammox process, was reported to be stable between pH 6.0 and 9.0, and was more active between pH 7.5 and 8.5 (Shimamura et al, 2007). In addition to soil pH, our results also indicated that soil EC, a parameter reflecting soil salinity, had a positive relationship with anammox rates and the functional gene abundance.…”
Section: Linkage Between Anammox Activity Bacterial Abundance and Somentioning
confidence: 56%
See 1 more Smart Citation
“…It was formed from oxidation of ammonia with the help of hydrazine hydrolase, and then converted to N 2 through hydrazine-oxidizing enzyme or hydroxylamine oxidoreductase (van de Graaf et al, 1997;Strous et al, 2006). The two enzymes were proposed to be different in (Strous et al, 1999a) Wastewater Candidatus Brocadia fulgida (Kartal et al, 2004) Wastewater Kuenenia Candidatus Kuenenia stuttgartiensis (Penton et al, 2006) Wastewater Scalindua Candidatus Scalindua brodae Wastewater Candidatus Scalindua wagneri Wastewater Candidatus Scalindua sorokinii Seawater Others Candidatus Jettenia asiatica (Tsushima et al, 2007) Not reported Candidatus Anammoxoglobus propionicus (Kartal et al, 2007) Synthetic water their specificities (Shimamura et al, 2007). Cytochromes were important electron transporters between enzymes (Huston et al, 2007).…”
Section: Metabolismmentioning
confidence: 99%
“…As enzimas hirazina-hidrolase estão envolvidas nesta via (sintetizadas pelo gene hh) (STROUS et al, 2006), como também a enzima hidroxilamina oxidorredutase (produto do gene hao), e a enzima hidrazina-oxidante (codificada pelo gene hzo) (SHIMAMURA et al, 2007). Desde a descrição do processo anammox (STROUS et al, 1999), várias bactérias foram identificadas como capazes de realizar essa transformação, todas pertencentes à ordem dos Planctomycetales, distribuídos em um clado monofilético com uma grande distância evolutiva de outros Planctomycetes.…”
Section: Introductionunclassified